Pengaruh Metode Resitasi terhadap Hasil Belajar Siswa dalam Mata Pelajaran Sejarah di SMAN 13 Padang - Putri Rahma Pertiwi; Wahidul Basri; Aisiah Aisiah (Journal of Education on Social Science (JESS), 2018)
This research aimed to know the influence of applying recitation learning method on students abilities in understanding of historical facts. The abilities were seen from student learning outcomes in written test. This was a quantitative research with experiment method. Data obtained from the learning tests result of students grade X IPS 1 SMAN 13 Padang. Population of this research consisted of three classes, and the sample consisted of two classes: grade X IPS 1 as experiment group and grade X IPS 3 as control group. The result of this research indicated that there was an influence of the application of recitation learning method on the historical learning outcomes of students grade X IPS 1 SMAN 13 Padang. The analysis of normality test showed that the population of the two samples normally distributed, while the homogeneity test showed that the sample had a homogeneous variant. Therefore, we can conclude that there was an influence of the application of recitation learning method on the historical learning abilities (outcomes) of students in SMAN 13 Padang.